IMPLEMENTASI PEMBELAJARAN NAHWU SHORROF DENGAN METODE AL-MIFTAH LIL ULUM DALAM UPAYA MENINGKATKAN PEMAHAMAN GRAMATIKA ARAB SANTRI DI PP MIFTAHUL ULUM IV (RU4) GANJARAN, GONDANGLEGI, MALANG - Abdur Rosidis Salami; Nur Qomari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the application of the al-Miftah lil-'Ulum method in improving the understanding of Arabic grammar (Nahwu and Shorrof) of students at the Miftahul Ulum IV Islamic Boarding School (RU4) Malang. The purpose of this study is to find out the extent to which the method can improve the grammatical ability and learning motivation of students. The research approach uses qualitative methods with data collection techniques through observation and semi-structured interviews with teachers and students, as well as analysis using the Miles and Huberman interactive model. The results of the study show that the al-Miftah lil-'Ulum method is effective in improving the ability of students to understand Arabic grammar through visual approaches, repetition, and contextual application. The use of colored tables, rule songs, and applied exercises increase students' involvement and confidence in reading classical texts. Despite obstacles such as limited facilities and variations in teacher discipline, routine evaluation and teacher commitment are able to maintain learning outcomes. Thus, the al-Miftah lil-'Ulum method has proven to be effective in strengthening the mastery of Arabic grammar and creating an active and pleasant learning atmosphere in the pesantren environment.